Mass spectrometric studies of estrogen receptors from largemouth bass (Micropterus salmoides) - Dancel, Maria Cristina Argel (ProQuest Information and Learning Company, 2006)
Estrogen receptors (ERs) are members of the nuclear steroid receptor superfamily of multi-domain proteins that initiate gene transcription through DNA and ligand binding. Previous studies using largemouth bass (LMB, Micropterus salmoides, have shown that both the male and female have three different ER mRNAs: fER[alpha], fER[beta] and fER[gamma]. These isotypes have unique tissue-expression patterns and probably control different sets of genes. To better understand their specific functions, it is important to measure the actual concentrations of the native proteins in various tissues. In this dissertation, proteomics and bioinformatics tools were used to identify characteristic peptides for the LMB ERs. Two of the ERs were expressed as recombinant proteins in E. coli and they served as external standards for method development. Intact proteins were analyzed by sodium dodecyl sulfate poly-acrylamide electrophoresis (SDS-PAGE) and the molecular weight was determined by matrix-assisted laser desorption time-of-flight mass spectrometry (MALDI-TOF-MS) in the linear mode. To further characterize these proteins, peptides were generated by in-gel trypsin digestion and analyzed by MALDI-TOF-MS in the reflectron mode. For this technique, picomole levels of recombinant fER[alpha] were needed. To develop the quantitation method online liquid chromatography electrospray mass spectrometry (LC-ESI-MS2) was used to identify unique tryptic fragments for fER[alpha]. Peptides were evaluated for their ion signal intensities and their specificities. From these peptides, the LIFAQDLILDR fragment was chosen as the best candidate and synthesized with a heavy-isotope labeled leucine at the seventh position. Results showed that LC-ESI-MS[superscript n] detected femtomole levels of the peptide standard and should enable quantitation of the native ERs in LMB tissues. Based on this work, automation and shorter sample preparation times are recom-mended for tissue preparation, ER isolation and MS analyses due to the short half-life of the receptor proteins and the higher abundance of oxidizable methionines compared to most cellular proteins. The same procedures can be used to develop peptide standards for the LMB ER beta and gamma.--Abstract.